Dairy farmers' knowledge, awareness, and practices regarding bovine lameness in Malaysian dairy farms - Sadiq, M. B.; Ramanoon, S. Z.; Mansor, R.; Syed Hussain, S. S.; Mossadeq, W. M. Shaik (Springer, 2024)
Given the data paucity on dairy farmers’ perspectives regarding bovine lameness and hoof diseases, particularly in South East Asian countries, this study was conducted to assess the knowledge, attitude and practices toward lameness and hoof health among dairy cattle farmers in Malaysia. An online-based and face-to-face survey was conducted among 114 dairy farmers from four states in Peninsular Malaysia. Data were analysed using descriptive statistics, principal component analysis and an independent sample t-test. Overall, farmers demonstrated satisfactory knowledge and attitude regarding lameness and its impact on dairy cattle welfare and production. Lameness was ranked the second most important health issue in dairy farms after mastitis. Notably, 90% reported the presence of at least one lame cow on their farms, and 55% stated lameness as the reason for culling their cows. While sole ulcer was the hoof lesion mostly identified by farmers, 75% of them underestimated lameness prevalence on their farms and rarely implemented management strategies such as preventive hoof trimming and footbath. Farmers’ educational qualification influenced their understanding of the impact of lameness on dairy cattle production. Despite reflecting satisfactory knowledge and attitude towards lameness in dairy cows, farmers in this study need to improve their current management practices to address lameness problem in their herds. Educating farmers on the importance of early detection and prompt treatment, and preventive measures are crucial for lameness control and improving hoof health in these dairy farms.